Toward an Ecology of Transfiguration : Orthodox Christian Perspectives on Environment, Nature, and Creation - Foltz, Bruce V.; Chryssavgis, John (Book collections on Project MUSE., 2013)
"Can Orthodox Christianity offer spiritual resources uniquely suited to the environmental concerns of today? This book makes the case emphatically that it can indeed. In addition to being the first substantial and comprehensive collection of essays, in any language, to address environmental issues from the Orthodox point of view, this volume (with contributions from many of the most influential theologians and philosophers in contemporary world Orthodoxy) will engage a wide audience, in academic as well as popular circles--resonating not only with Orthodox audiences but with all those in search of a fresh approach to environmental theory and ethics that can bring to bear the resources of ancient spirituality, often virtually unknown in the West, on modern challenges and dilemmas"--